Miniaturized Wideband Bandpass Filter with Wide Stopband using Metamaterial-based Resonator and Defected Ground Structure - Chaimool, Sarawuth; Akkaraekthalin, Prayoot (Společnost pro radioelektronické inženýrství, 2012)
This paper presents a miniaturized wideband bandpass filter with wide stopband performance. It is shown that the coupled metamaterial-based resonators (MBRs) incorporating with the defected ground structure (DGS) can significantly increase the coupling value to achieve wideband bandpass filter. This technique has been extended to realize wideband bandpass filter having fractional bandwidth of 63 % and low insertion loss in the passband. To further suppress the spurious harmonics and upper stopband, the combining of the zero-degree feed structure and embedded slot-loaded resonators in both input and output ports is introduced. The proposed filter has not only compact size but also good out-of-band response. The experimental results are demonstrated and discussed.
Keywords: Wideband bandpass filter; Metamaterial; Suppress harmonics; Upper stopband; Defected ground structure